2010
DOI: 10.1093/jat/34.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Drug Toxicity Caused by the Coadministration of 4-Methylmethcathinone (Mephedrone) and Heroin

Abstract: An accidental death caused by the combined use of a new designer drug, 4-methylmethcathinone (mephedrone), and heroin is reported. A 22-year-old Caucasian male was found unresponsive in his living quarters and was transported to the hospital where he died. During autopsy, needle marks were found along the decedent's lower legs and ankles. Investigators discovered the decedent and his roommate had been using "Black Tar" heroin and mephedrone. Routine toxicological analysis detected morphine in the decedent's bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 0 publications
5
76
0
4
Order By: Relevance
“…However, its relatively short duration of action, which lead to repeated dosing, is more similar to cocaine (Wilkinson et al 1980). In a recent study, 70 % of mephedrone users reported to be using it by nasal insufflation, while 30 % admitted to be taking it orally (Dickson et al 2010;Winstock et al 2011). There are numerous reports of individuals using mixed routes during a single session.…”
Section: Introductionmentioning
confidence: 99%
“…However, its relatively short duration of action, which lead to repeated dosing, is more similar to cocaine (Wilkinson et al 1980). In a recent study, 70 % of mephedrone users reported to be using it by nasal insufflation, while 30 % admitted to be taking it orally (Dickson et al 2010;Winstock et al 2011). There are numerous reports of individuals using mixed routes during a single session.…”
Section: Introductionmentioning
confidence: 99%
“…Four additional mephedronerelated deaths are reported: stab wounds were the cause of death in one, mephedrone responsible for two, and the other case unresolved [34]. Accidental death due to multidrug toxicity occurred after use of mephedrone and heroin in a 22-year-old male [32]. Mephedrone was thought to be the cause of death in a person with excited delirium that was aggravated by blood loss from wounds sustained from breaking windows.…”
Section: Mephedronementioning
confidence: 99%
“…Urine drug screening in another series found that 16 of 17 specimens were positive for other drugs of abuse [13]. Postmortem toxicology testing has also revealed that concurrent use of other substances is common [32][33][34] Adverse Clinical Effects of Synthetic Cathinones Cardiac, psychiatric, and neurological signs and symptoms are the most common adverse effects reported in synthetic cathinone users who require medical care. There are four series detailing clinical effects of cathinones.…”
Section: Subjective User Effectsmentioning
confidence: 99%
“…Previously, a Danish teenager found in possession of mephedrone died in May 2008, although toxicology reports were inconclusive (Campbell, 2009). The first mephedrone-related death in the USA involved the combined use of mephedrone and heroin (Dickson et al, 2010). More recently, the first cases from the Netherlands (Lusthof et al, 2011) and the Republic of Ireland (EMCDDA, 2011:85) have been reported.…”
Section: Fatalitiesmentioning
confidence: 99%